2018 2nd URSI Atlantic Radio Science Meeting (AT-RASC) 2018
DOI: 10.23919/ursi-at-rasc.2018.8471315
|View full text |Cite
|
Sign up to set email alerts
|

On the Observational Properties of the Decameter Striae

Abstract: In the paper we present the preliminary results of analysis of the solar Type IIIb bursts properties observed on June 14, 2012. Namely the parameters of their fine structure known as striae are studied in the continuous frequency band 8 -32 MHz. It is shown that durations and instantaneous frequency bandwidths depend on the observing frequency. Notably, bandwidth increases and duration decreases with the frequency. The comparative analysis of the decameter spikes and striae is also performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The average value of the Type IIIb bursts polarization varied from 40% ± 10% to 60% ± 10% depending on the day of observation and its sign coincided with the polarization sign of the associated Type III bursts. This result along with the results presented in (Shevchuk et al, 2018) might be additional evidence that spikes and striae, which form Type IIIb burst, are apparently the same type of the solar radio bursts.…”
Section: Analysis Of the Observational Datasupporting
confidence: 79%
“…The average value of the Type IIIb bursts polarization varied from 40% ± 10% to 60% ± 10% depending on the day of observation and its sign coincided with the polarization sign of the associated Type III bursts. This result along with the results presented in (Shevchuk et al, 2018) might be additional evidence that spikes and striae, which form Type IIIb burst, are apparently the same type of the solar radio bursts.…”
Section: Analysis Of the Observational Datasupporting
confidence: 79%
“…The sense and degree of polarization of decameter spikes agree well with those obtained for the decameter Type IIIb bursts. This fact can be additional evidence that spikes and striae, which form Type IIIb bursts, are the same type of the solar radio bursts [Shevchuk M. V., et al, 2018].…”
Section: Resultsmentioning
confidence: 67%
“…However, a considerably wider frequency band of available observational data allowed to determine the dependences of striae durations and bandwidths on frequency. Thus it was found that the straie durations decreased with increasing frequency as On basis of the results obtained and assuming the plasma emission mechanism the authors supposed that the durations and the bandwidths of stria bursts were apparently determined by the temperature and the magnetic fi eld in the place of generation, just as it took place for the decameter spikes [20]. The mean temperature obtained under such assumptions equaled to 0.28 K, and the magnetic fi eld was approximately 1.8 G at the distance of 1.9 .…”
Section: Type Iiib-iiid Burstsmentioning
confidence: 94%
“…It was shown that the Type IIIb bursts were predominantly observed simultaneously with the Type III bursts and consisted of a number of separate striae [19,20]. The total amount of individual striae in one Type IIIb burst in the frequency range of 8 32  MHz could exceed 95.…”
Section: Type Iiib-iiid Burstsmentioning
confidence: 99%